Черная метка - Папоров Юрий Николаевич (Пираты Карибского моря, 2007)
7-10кл Экземпляры: ф.8 (20161117) / Инвентарный номер: 57269 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: П 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44